RECALL ELECTION MELALUI PERADILAN SEBAGAI MEKANISME DEMOKRATISASI PASCA PEMILU - Bima Rico Pambudi; Moch. Marsa Taufiqurrohman; Mohammad Ircham Maulana (Mimbar Hukum, 2023)
Abstract The people’s lack of role and participation in directly monitoring the running of the government after the general election needs to be reviewed. The general election process continues beyond the pre-election and during the election process. The general election process also includes post-election processes. Even though in a democracy, the people occupy the highest position in the constitutional system, their role in government has only been considered limited before and during general elections. This article aims to provide the people with an effective and efficient way to get involved in government as a form of post-election democratic process. This article provides insight for a method of popular participation after the general election. By combining normative juridical research methods and reform- oriented research, this article aims to examine the probability of implementing the Recall Elections method as a form of effort to increase the role of the people after the general election. An example of a form of effort through Recall Elections is direct supervision by the people of their representatives elected in the general election process. Ultimately, this article considers several options for developing normative and political strategies for implementing Recall Elections as a form of post-election widespread democratization in Indonesia. Abstrak Minimnya peran dan partisipasi rakyat dalam memantau langsung jalannya pemerintahan pasca pemilihan umum (Pemilu) perlu dikaji ulang. Proses Pemilu tidak hanya terhenti pada proses pra dan pada saat pemilihan. Proses Pemilu juga mencakup proses pasca Pemilu. Meskipun dalam negara demokrasi rakyat menduduki kedudukan tertinggi dalam sistem ketatanegaraan, peran rakyat dalam pemerintahan hanya dianggap terbatas sebelum dan pada saat pemilihan umum. Artikel ini bertujuan untuk memberikan rakyat cara yang efektif dan efisien untuk terlibat dalam pemerintahan sebagai bentuk proses demokrasi pasca Pemilu. Artikel ini mencoba memberikan wawasan tentang kebutuhan sebuah metode partisipasi rakyat pasca pemilihan umum. Dengan menggunakan metode penelitian normatif-doktrinal, artikel ini bertujuan untuk mengkaji kemungkinan penerapan metode Recall Elections sebagai bentuk upaya peningkatan peran masyarakat pasca Pemilu. Salah satu bentuk peningkatan peran masyarakat pasca Pemilu melalui Recall Elections adalah pengawasan langsung oleh rakyat terhadap wakil-wakilnya yang telah dipilih dalam proses Pemilu. Puncaknya, artikel ini mempertimbangkan beberapa opsi untuk mengembangkan strategi normatif dan politik dalam melaksanakan Recall Elections sebagai bentuk demokratisasi yang meluas pasca Pemilu di Indonesia.